Radical conservatism and circumstantial multiculturalism: Jews, Christians and Muslims in a French Catholic School in Israel. Issue 9 (21st October 2022) - Levy, Natalie; Monterescu, Daniel
ABSTRACT: The French Saint-Joseph school in Jaffa is one of the few educational institutions in Israel that have survived, since 1882, three political regimes without relinquishing pedagogical or managerial autonomy. This article examines the emergence of circumstantial multiculturalism in the midst of radical political changes in a colonial-international school. Since 1948, the school has been founded on three constitutive contradictions: a Catholic school with a majority of Muslim and Jewish students; a French school whose vast majority of pupils are not native French speakers; and a colonial school designed to serve the French metropole and the interests of the Catholic Church, but which has been catering for the changing local elites. We show how the school produces a conservative pedagogical space that preserves religious and cultural recognition through a policy of de-politicization. The combination of pedagogical conservatism and pragmatic institutional pluralism posits a radical educational alternative to Israel's public-school system and a political alternative to multicultural policy.